2016
DOI: 10.1002/hlca.201600125
|View full text |Cite
|
Sign up to set email alerts
|

Megastigmane Glycosides from Docynia indica and Their Anti‐inflammatory Activities

Abstract: Using various chromatographic methods, three new megastigmane glycosides, docynicasides A – C (1 – 3) and ten known, (6S,9R)‐vomifoliol 9‐O‐β‐d‐xylopyranosyl‐(1′′→6′)‐O‐β‐d‐glucopyranoside (4), hyperin (5), quercitrin (6), quercetin 3‐α‐l‐arabinofuranoside (7), naringenin 7‐O‐β‐d‐glucopyranoside (8), phloridzin (9), phloretin 2′‐O‐β‐d‐xylopyranosyl‐(1→6)‐β‐d‐glucopyranoside (10), pinosylvin 3‐O‐β‐d‐glucopyranoside (11), tormentic acid (12), and chlorogenic acid methyl ester (13) were isolated from the fruits o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Avicularin, also known as quercetin 3-O-α-L-arabinofuranoside, is a flavonoid and quercetin derivative (Guo et al, 2018). Compared with quercetin, avicularin has a stronger anti-inflammatory ability (Dung et al, 2016). The excessive secretion of cytokines in an inflammatory state will lead to depression.…”
Section: Avicularinmentioning
confidence: 99%
“…Avicularin, also known as quercetin 3-O-α-L-arabinofuranoside, is a flavonoid and quercetin derivative (Guo et al, 2018). Compared with quercetin, avicularin has a stronger anti-inflammatory ability (Dung et al, 2016). The excessive secretion of cytokines in an inflammatory state will lead to depression.…”
Section: Avicularinmentioning
confidence: 99%
“…The fruits of D. indica have been used in traditional remedies for the treatment of infectious diseases, digestive disorders, dyhypeslipidemia, and hypertension [1,2]. It was also found to possess biological activities, including anti-inflammatory [3], antioxidant and antimicrobial [4], The study results showed that the fruits of D. indica contain flavonoids, triterpenoids and megastigmane glycosides [3,5]. Catechin and ferulic acid were the major phenolics present in D. indica fruits [4].…”
Section: Introductionmentioning
confidence: 99%